2014
DOI: 10.2478/hukin-2014-0040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength Training Combined with Specific Plyometric exercises on body composition, vertical jump height and lower limb strength development in elite male handball players: a case study

Abstract: The purpose of the present study was to identify the effects of a strength training program combined with specific plyometric exercises on body composition, vertical jump (VJ) height and strength development of lower limbs in elite male handball players. A 12-week program with combined strength and specific plyometric exercises was carried out for 7 weeks. Twelve elite male handball players (age: 21.6 ± 1.73) competing in the Portuguese Major League participated in the study. Besides the anthropometric measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 30 publications
1
31
0
3
Order By: Relevance
“…Gorostiaga et al [15], for instance, found gains of 13% and 9% in leg extensor and flexor muscles, respectively, after a 6-week period of heavy training. Similarly, Carvalho et al [24] showed an improvement in the peak torque of thigh muscles and concentric ratio after a 4-week heavy training program. Likewise, most strength variables increased between the two moments of assessment; however, the most significant differences were found with the knee isometric left antagonist (11.4%), eccentric left agonist (9.6%), isometric right agonist (8%) and eccentric right antagonist (6.6%).…”
Section: Isokinetic Strengthmentioning
confidence: 78%
See 1 more Smart Citation
“…Gorostiaga et al [15], for instance, found gains of 13% and 9% in leg extensor and flexor muscles, respectively, after a 6-week period of heavy training. Similarly, Carvalho et al [24] showed an improvement in the peak torque of thigh muscles and concentric ratio after a 4-week heavy training program. Likewise, most strength variables increased between the two moments of assessment; however, the most significant differences were found with the knee isometric left antagonist (11.4%), eccentric left agonist (9.6%), isometric right agonist (8%) and eccentric right antagonist (6.6%).…”
Section: Isokinetic Strengthmentioning
confidence: 78%
“…The initial search yielded 2570 studies. Finally, after deleting duplicates and based on inclusion/exclusion criteria, 18 studies [5][6][7][8][9][10][13][14][15]17,[19][20][21][22][23][24][25][26] were retained in the present systematic review and meta-analysis ( Figure 1). The main features of the studies are presented in Table 2.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…12 This action of deceleration to acceleration is known as the stretch-shortening cycle. A greater power output can be found when the stretch-shortening cycle is used because of the efficiency gained by releasing elastic energy stored in the muscles.…”
mentioning
confidence: 99%
“…The effects of strength training together with limitation in blood flow seems to be an outcome of the consistency between the blood occlusion (external cuff pressure), the muscle's electric activity (rise in signaling electromyography), and exhaustion level (which could be continuous) [9]. Carvalho et al studied 12 handball players aged 21 during 12 weeks of strength training accompanied by plyometric exercises and found a significant rise in their records in squat jump, long jump, and 40 subsequent jumps [10].…”
Section: Introductionmentioning
confidence: 99%